The application of braced and unbraced frames in reinforced concrete structures - Bakhtiar, Nur Wahida (2014)
Many designers are uncertain whether a building with a certain height should be designed with shear walls. Some believe that the buildings of up to about ten storeys height need to be provided with shear wall. This project was carried out to study the suitability of reinforced concrete structures to be designed as braced or unbraced. The analysis was done on two series of identical model buildings with five, ten and 15 storeys each. Both series were subjected to the same vertical and horizontal loads. The analysis was carried out using Orion 18 software. The performances of the structures were measured in terms of bending moment carried by the members and the quantity of steel reinforcement required from which comparisons between the braced and unbraced buildings were made. The opinion from the practicing structural engineers on the matter was also sought through questionnaires sent to them. The results show that in the low rise buildings the moments in the major structural elements and the quantity of steel reinforcement required in braced and unbraced buildings are about the same. For higher rised buildings the difference becomes significant with larger value found in the unbraced buildings. The results also suggested that the buildings of up to 12 storey height can still be designed as unbraced structures, while those taller than 12 storeys should be designed as braced structures